Industri Televisi Swasta Indonesia dalam Perspektif Ekonomi Politik - Setio Budi HH (FISIP Universitas Atma Jaya Yogyakarta, 2004)
The presence of commercials television in Indonesia had many dynamics. Some background shown the development of commercial television, first it was rise from the government problems facing with spillover of transnational broadcasting via parabola antenna, second, the pressured of the international institutions relating with regulations—liberalization (against the state monopoly of media–TVRI), third, the pressured of national business entities (after the restriction of advertising in television, 1980). This article questions therefore what is the implications of commercial televisions in Indonesia, especially to the public that seems didn’t have voice enough for the presence of the those commercial elevisions.